2005
DOI: 10.1002/pola.21071
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of classical surfactants and polymerizable surfactants (surfmers) in the reversible addition–fragmentation chain transfer mediated miniemulsion polymerization of styrene and methyl methacrylate

Abstract: Cationic and anionic amphiphilic monomers (surfmers) were synthesized and used to stabilize particles in miniemulsion polymerization. A comparative study of classical cationic and anionic surfactants and the two surfmers was conducted with respect to the reaction rates and molecular weight distributions of the formed polymers. The reversible addition–fragmentation chain transfer process was used in the miniemulsion polymerization reactions to control the molecular weight distribution. The reaction rates of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 59 publications
1
48
0
1
Order By: Relevance
“…76), are effective with styrenic and acrylic monomers. Recent work [54,55] has focussed on the relative effectiveness of a series of dithiocarbamates where the nitrogen lone pair is part of a heteroaromatic ring system (78)(79)(80)(81)(82)(83)(84)(85) in controlling polymerization of styrene. Of these, compounds 84 and 85, where there is little delocalization of the lone pair into the aromatic system, were not effective as RAFT agents.…”
Section: Choice Of Raft Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…76), are effective with styrenic and acrylic monomers. Recent work [54,55] has focussed on the relative effectiveness of a series of dithiocarbamates where the nitrogen lone pair is part of a heteroaromatic ring system (78)(79)(80)(81)(82)(83)(84)(85) in controlling polymerization of styrene. Of these, compounds 84 and 85, where there is little delocalization of the lone pair into the aromatic system, were not effective as RAFT agents.…”
Section: Choice Of Raft Agentsmentioning
confidence: 99%
“…10* EEA [77] BMA [78] BzA [78] 11* (DBI) [64] DMA [72] HPMAM [80] 12a* R = H BzMA [78] DMAEMA [78] EHA [78] MMA [81] PEGMA [72] PFMA [73] S [81] 12b R = CH 3 [83] AM [83] TMAEMA [83] MA [78] MMA [78,79] tBA [78] XMA [82] S…”
Section: Characterization Of Raft-synthesized Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…A Tabela 1 apresenta os estudos publicados até a presente data sobre a produção de polímeros que utilizaram a técnica RAFT em miniemulsão. Conforme revisado, a técnica de polimerização RAFT em miniemulsão já foi adaptada para os principais tipos de monômeros comerciais (como, por exemplo, estireno [28,34,35, , metacrilato de metila [35,54,68,[74][75][76][77][78][79][80] ), sistemas inversos [23,52,[81][82][83][84][85][86] e sistemas contínuos de polimerização [87][88][89] ). Além dos trabalhos citados na P(AM-co-AA) Inverso [83] P(NIPAM-b-PEO) Inverso [82] a Poliestireno (PSt), poli(metacrilato de metila) (PMMA), poli(buitl metacrilato (PnBMA), poli(hidroxietil metacrilato) (PEHMA), poli(butil acrilato) (PnBA), poli(acetato de vinila) (PVAc), Poliacrilamida (PAM), poli(ácido acrílico), poli(2-dimetilamino (metacrilato de etila)) (PDMAEMA), ácido metacrílico (MAA), acrilato de dodecafluoro heptil (DFHA), acrilamida (AM), ácido acrílico (AA), isopopil acrilamida (NIPAM), poli(óxido de etileno) (PEO).…”
Section: Polimerização Raft Em Miniemulsãounclassified
“…These results spurred us to explore the feasibility of using reactive surfmer, i.e., alkyne-bearing surfmer, to introduce the alkyne moieties onto the surface of polymer particles via enzymatic miniemulsion polymerization in a one-pot procedure at room temperature. While there were some pioneer works of miniemulsion polymerization with a functional surfmer to prepare polymer particles [24][25][26][27][28][29][30][31], only one study on post-functionalization of particles surface based on surfmer was found in the literature [32]. Froimowicz and Landfester reported that the preparation of particles by miniemulsion polymerization with phosphonate surfmer, and phosphonate functionalized obtained particles were used as functional scaffolds allowing the binding of calcium ions to subsequently mineralize hydroxyapatite on the surface of the particles.…”
Section: Introductionmentioning
confidence: 99%